Tree-Ring Evidence of Forest Management Moderating Drought Responses: Implications for Dry, Coniferous Forests in the Southwestern United States - van Mantgem, Phillip J.; Kerhoulas, Lucy P.; Sherriff, Rosemary L.; Wenderott, Zachary J. (Frontiers in Forests and Global Change, 2020)
Drought, coupled with rising temperatures, is an emerging threat to many forest types across the globe. At least to a degree, we expect management actions that reduce competition (e.g., thinning, prescribed fire, or both) to improve growth of residual trees during drought. The influences of management actions and drought on individual tree growth may be measured with high precision using tree-rings. Here, we summarize tree-ring-based assessments of the effectiveness of thinning and prescribed fire as drought adaptation tools, with special consideration for how these findings might apply to dry coniferous forests in the southwestern U.S. The existing literature suggests that thinning treatments generally improve individual tree growth responses to drought, though the literature specific to southwestern coniferous forests is sparse. Assessments from studies beyond the southwestern U.S. suggest treatment effectiveness varies by thinning intensity, timing of the drought relative to treatments, and individualistic species responses. Several large-scale studies appear to conflict on specifics of how site aridity influences sensitivity to drought following thinning. Prescribed fire effects in the absence of thinning has received much less attention in terms of subsequent drought response. There are limitations for using tree-ring data to estimate drought responses (e.g., difficulties scaling up observations to stand- and landscape-levels). However, tree-rings describe an important dimension of drought effects for individual trees, and when coupled with additional information, such as stable isotopes, aid our understanding of key physiological mechanisms that underlie forest drought response.